Halal Destinations Brand Equity: Impacts on Tourist Motivation and Travel Revisit Intention in Indonesia - Sasmitawidjaja, Vinesya; Sobari, Nurdin (Ekonomi Syariah IAIN Kudus, 2025)
The purpose of this study is to determine how the brand equity of Indonesia's ten halal destinations affects tourists' motivation and intention to revisit. Grounded in the Theory of Planned Behavior (TPB) and the Islamic marketing framework, this study integrates both behavioral and spiritual dimensions to explain tourist decision-making in halal destinations. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.9 as the analytical tool. Data were collected from 413 valid responses of domestic tourists from Generations X and Y (aged 27–56) who had visited at least one of Indonesia’s halal destinations in the last five years. Purposive sampling was used to ensure respondents met the halal travel criteria. The results revealed that perceived quality, value, and loyalty of halal destinations positively and significantly affect halal destination brand equity, while awareness and image have insignificant effects. Furthermore, halal destination brand equity significantly influences tourist motivation and intention to revisit, confirming its mediating role between destination attributes and behavioral outcomes. The novelty of this research lies in integrating Islamic values, such as ihsan (service excellence) and tayyib (goodness), into the halal destination brand equity framework, thereby offering a holistic understanding of spiritual–behavioral alignment. The findings provide theoretical and managerial implications for strengthening Indonesia’s position as a leading global halal tourism destination.